Service Innovation "Kelink Emas" (Community Internet Linked Health Consultation) in The Center Of Public Healthin Sukomoro, Nganjuk District - Fitrotun Niswah; Eva Hany Fanida; Tauran Tauran; Trenda Aktiva Oktariyanda; Suci Megawati; Deby Febriyan Eprilianto; Trisna Anggun Cahyaningtyas (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
As a public service provider, the government is required to provide the best service for citizens. One of the services that must receive attention is health service. In order to improve the quality of health services, the Sukomoro Community Health Center created a service innovation, namely the KelinkEmas (Community Internet-linked Health Consultation). One of the factors behind this innovation is the slow response of the government to public complaints. In addition, the outbreak of the Covid-19 pandemic has made people eager to look for the correct information and consult on health without face to face to avoid the risk of Covid-19. Therefore, this research aims to analyze the KelinkEmas services at the Sukomoro Community Health Center. This is descriptive research with a qualitative approach. The results showed that the KelinkEmas service innovation provided comprehensive online health services, including health information services, health centre policies, general polyclinics, nursing care, nutritional care, midwifery care, laboratories, mental health, Covid-19, adolescent health, hajj health, elderly health, environmental health, oral health, emergency room, inpatient care, and pharmacy. Through the support of a culture of innovation, the readiness of tools and instruments, the KelinkEmas innovation is expected to be an alternative health service solution during the Covid-19 pandemic. Keywords:1 Service Innovation, Health Services, Kelink Emas.